Parents and end-of-life decision-making for their child: roles and responsibilities. Issue 3 (4th March 2014) - Sullivan, Jane; Gillam, Lynn; Monagle, Paul
Abstract : Background: Whether parents want to be and should be the decision-maker for their child in end-of-life matters are contested clinical and ethical questions. Previous research outcomes are equivocal. Method: A qualitative interview method was used to examine the views and experiences of 25 bereaved parents in end-of-life decision-making for their child. Data were analysed thematically. Results: Three types of decision-making roles were identified: self-determined, guided (both involving active decision-making) and acquiescent (passive).The majority of parents had been active in the decision-making process for their child. They perceived themselves as the ultimate end-of-life decision-maker. This was perceived as part of their parental responsibility. A minority of parents did not consider that they had been an active, ultimate decision-maker. Generally, parents in the self-determined and guided groups reported no negative consequences from their decision-making involvement. Importantly, parents in the acquiescent group described their experience as difficult at the time and subsequently, although not all difficulties related directly to decision-making. Parents considered that in principle parents should be the end-of-life decision-maker for their child, but understood personal characteristics and preference could prevent some parents from taking this role. Conclusions: This study unequivocally supports parents' desire to fulfil the end-of-life decision-making role. It provides a nuanced understanding of parents' roles and contributes evidence for the ethical position that parents should be the end-of-life decision-makers for their child, unless not in the child's best interests. On the whole, parents want this role and can manage its consequences. Indeed, not being the end-of-life decision-maker could be detrimental to parents' well-being.